Insights into the Process of Gas Release from Organic-Rich Shale: Release Characteristics and Controlling Factors - Fei Li; Wei Dang; Fengqin Wang; Haikuan Nie; Yubo Feng; Qiubo Liu; Jiangtao Sun; Yao Ma (Geofluids)
Shale gas release in canister can significantly enrich our understanding in gas-in-place characteristics. However, studies on shale gas release characteristics and its controlling factors are rare. In this study, gas release curves of 52 shale samples and 3 coal samples were measured using wellsite canister testing technique. According to curve shape, three curve patterns including L-shaped, S-shaped, and M-shaped are identified, and the difference among three curve patterns mainly lies in the fractional gas volume released in surface temperature stage. To evaluate the dependence of released gas content on shale properties, the variation in released gas content with organic matter, minerals, porosity, permeability, specific surface area, and pore volume is analyzed and found that the released gas content shows a strong dependence on the properties that control or could increase gas adsorption and diffusion capacity, such as TOC content, specific surface area, and permeability, while showing no dependence on the properties that control free gas storage capacity, such as minerals, porosity, and pore volume. Additionally, correlations of released gas content with adsorbed/free gas show that the released gas during canister testing is the gas that was in the adsorbed state in reservoir, and the free gas has been lost during coring, as well as a fraction of adsorbed gas. Above findings provide insightful information not only on gas-in-place evaluations but also on the dynamic behavior of adsorbed/free gas from producing well.